Aprendizagem significativa: a relação de estudantes de Benjamin Constant - AM com a química em um contexto ambiental - Barros, Almir de Souza (Brasil, 2021)
The Potentially Significant Teaching Unit – UEPS constructed is a sequence of activities based on the Theory oh Meaningful Learning, which, in Brazil, one of the main scholars oh this theory is Marco Antônio Moreira; however, it has as its main precursor, David Ausubel. Based on Ausubel’s theory, the presente applied research in education was developed to encourage practce in a public school in the city of Benjamin Constant – AM. Meaningful learning is understood as the process through which new information (new knowledge) is related in a nonarbitray and substantive (non-literal) way to the learner’s cognitive structure. For this reason, there was na interest in combining the theory’s precepts with environmental issues, mainly because it provides students from the public school system with better knowledge of the region in which they live, seeking to awaken in them a critical sense through discussions of the environmental problems nad in addition to enabling them to learn meaningfully. UEPS was to discuss the environmental issues experienced by students and relate them to scientific convepts about plastics and polymers in Chemistry classes. The work presented elements of action research oh the pratical type and also of bibliographical research, which is presente from the Project elaboration and continued until the end of the research. The approach was qualitative, in which the main focus is to get in touch with the environment and with the people who are in it. The method used was deductive, based on theories and laws considered general and universal,seeking to explain the occurrence of particular phenomena. After the elaboration of UEPS, it was made available through digital media for schools and teacheres to use in their classes aimed at 3er year high school classes in schools in the city of Benjamin Constant – AM. After analyzing and discussing the elaboration of the UEPS, it was possible to asses show this material contributes to a significant learning of the concepts we proposed to work on, in addition to obtaining evidence of a possible conceptual evolution by the students.